2016
DOI: 10.1080/10407413.2016.1230372
|View full text |Cite
|
Sign up to set email alerts
|

Articulating What Infants Attune to in Native Speech

Abstract: To become language users, infants must embrace the integrality of speech perception and production. That they do so, and quite rapidly, is implied by the native-language attunement they achieve in each domain by 6–12 months. Yet research has most often addressed one or the other domain, rarely how they interrelate. Moreover, mainstream assumptions that perception relies on acoustic patterns whereas production involves motor patterns entail that the infant would have to translate incommensurable information to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
41
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(43 citation statements)
references
References 185 publications
(275 reference statements)
2
41
0
Order By: Relevance
“…It can be hypothesized that place of articulation is perhaps learned earlier and as fast as manner of articulation if training not uses only auditory information but somatosensory information as well. This hypothesis is in line with the Articulatory Organ Hypothesis (Tyler et al, 2014; Best et al, 2016) which stresses the importance of the role of active articulators in production also for perception and thus for speech learning already in the first year of lifetime. Indeed an earlier and faster separation of syllables with respect to place of articulation and thus an earlier and faster learning of this feature has been found in this study for the case of availability of auditory and somatosensory information compared to the case of auditory information only.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…It can be hypothesized that place of articulation is perhaps learned earlier and as fast as manner of articulation if training not uses only auditory information but somatosensory information as well. This hypothesis is in line with the Articulatory Organ Hypothesis (Tyler et al, 2014; Best et al, 2016) which stresses the importance of the role of active articulators in production also for perception and thus for speech learning already in the first year of lifetime. Indeed an earlier and faster separation of syllables with respect to place of articulation and thus an earlier and faster learning of this feature has been found in this study for the case of availability of auditory and somatosensory information compared to the case of auditory information only.…”
Section: Discussionsupporting
confidence: 83%
“…If we assume that only a sparse phonological representation exists at the beginning of speech acquisition (cf. Best et al, 2016), the emergence of the action repository as well as of the mental lexicon has to start with a sparse organization at the beginning of the acquisition process. Therefore we developed an approach comprising a direct neural association between conceptual lexical and sensorimotor syllabic representations of speech items.…”
Section: Introductionmentioning
confidence: 99%
“…The ecological dynamics approach to speech production is best represented by articulatory phonology (Browman & Goldstein, 1992, and subsequent), a task-dynamic approach to articulation (Kelso et al, 1986;Saltzman & Kelso, 1987;Saltzman & Munhall, 1989), and by ecological theories of speech perception (Best, 1995;Fowler, 1986;Galantucci et al, 2006;Goldstein & Fowler, 2003) and speech sound acquisition (Best, 1995;Best, Goldstein, Nam, & Tyler, 2016). The fundamental unit of analysis is a vocal tract constriction that serves as an articulatory attractor.…”
Section: The Ecological Dynamics Approachmentioning
confidence: 99%
“…This unit is known as a gesture. Gestures are linguistic primitives, similar to distinctive features in generative theory, that emerge during development under the assumption that infants acquire "a relation between actions of distinct (articulatory) organs and lexical units very early in the process of developing language" (Goldstein & Fowler, 2003, p. 35; see also Best et al, 2016). Gestures are defined as "events that unfold during speech production and whose consequences can be observed in the movements of the speech articulators" (Browman & Goldstein, 1992, p. 156).…”
Section: The Ecological Dynamics Approachmentioning
confidence: 99%
“…In addition to motor resonance, recent studies have also shown pervasive connections between speech perception and production (e.g. Best, Goldstein, Nam, & Tyler, 2016;Schmitz, Díaz, Rubio, & Sebastian-Galles, 2018). According to these accounts, vocal imitation may therefore be facilitated by watching…”
Section: Introductionmentioning
confidence: 99%